Ответы и объяснения

2013-03-18T16:51:15+00:00

S(13)=-4*(1/2^13-1)/-0.5

S(13)=4*(1/2^13-1)/0.5

 

а дальше  фигово, видимо ку  другое

2013-03-18T17:13:31+00:00

Sn=\frac{b1*(q^{n}-1)}{q-1}

S13=\frac{-4*((\frac{1}{2})^{13}-1)}{\frac{1}{2}-1}=\frac{-4*(\frac{1}{2048}-1)}{-\frac{1}{2}}=\frac{-4*(-\frac{2047}{2048})}{-\frac{1}{2}}=\frac{-4*(-\frac{2047}{2048})}{-\frac{1}{2}}=\frac{\frac{2047}{512}}{-\frac{1}{2}}=\frac{2047}{512}:(-\frac{1}{2})=\frac{-2047*2}{512}=\frac{-2047}{256}

Да, дальше действительно фигово)

Или тогда вот такой вот ответ:  -7\frac{255}{256}